Social media engagement in health and climate change: an exploratory analysis of Twitter - Su Golder; Hilary Graham (IOP Publishing, 2024)
Social media are increasingly used by the public to share information and opinions. This study explores social media engagement in health and climate change through an analysis of English-language posts on Twitter, one of the most widely-used platforms. We searched Twitter from 21 March 2023 to 11 May 2023 for posts related to climate change using climate-related textwords and hashtags; we then used health keywords ('health', 'wellbeing', 'illness', 'illnesses', 'disease', 'death') to identify posts related to health. Focusing on posts from general public users, we investigated the proportion of climate change posts referring to health and, for a random sample of these tweets, undertook a content analysis to identify the ways in which climate change and health were represented. The content analysis drew on media research on 'framing', a selective process through which particular aspects of an issue-for example, its causes, impacts and solutions-are highlighted. 668 810 posts related to climate change were posted during the study period. Health-related text words were included in 2.3% (15 434) of these posts. The content analysis pointed to two divergent frames. The first frame represents climate change as real, with real effects on people's health. The second frame portrays climate change as a hoax, with hoax-generated health effects. While the 'reality' frame does not engage with the hoax frame, the latter provides an insistent counter-narrative that questions trust in mainstream science and government policy. Neither frame engages with people's experiences of health and climate change. In conclusion, our study points to low levels of engagement in health in a key forum for public discussions about climate change. It also asks whether the failure of the 'reality' frame to engage either with people's lived experiences or with hoax framings may be contributing to a polarised debate about climate change and health and hindering consensus-building.